Nonclinical evaluations of deucravacitinib and Janus kinase inhibitors in homeostatic and inflammatory pathways - Johnson, Brandon; Cheng, Lihong; Koenitzer, Jennifer; Catlett, Ian M.; Schafer, Peter (Frontiers in Immunology, 2024)
Translational medicine provides insight into novel drugs and predicts unwanted effects. In well-characterized pathways (e.g., cytokine-Janus kinase [JAK]-signal transducers and activators of transcription [STAT]), a variety of in vitro assessments were used to estimate selectivity of effects on different potential targets (i.e., JAK1, JAK2, JAK3, and tyrosine kinase 2 [TYK2]). Several approved drugs were characterized as selective for the JAK family. These assessments are challenged by a lack of compounds that only inhibit one JAK family member. Deucravacitinib is a first-in-class, oral, selective, allosteric inhibitor of TYK2, a kinase required for IL-12, IL-23, and Type I interferon signaling. Unlike deucravacitinib, which selectively binds to the TYK2 regulatory domain, JAK1,2,3 inhibitors target the catalytic domain, contributing to nonselective targeting of JAK1,2,3. Cytokines associated with JAK1,2,3 signaling are required for both immune and nonimmune functions. A similar laboratory abnormality profile was observed in clinical trials using JAK1,2,3 inhibitors that has not been observed with deucravacitinib. In vitro testing of JAK1,2,3 inhibitors has relied upon assays of signal transduction, such as those measuring STAT phosphorylation, for estimates of potency and selectivity. These assay systems can be effective in estimating in vivo efficacy; however, they may not provide insight into downstream outcomes of receptor signaling, which may be more relevant for evaluating safety aspects. Assay systems assessing functional outcomes from cells may yield a more useful translational evaluation. Here, deucravacitinib was assessed for potency and selectivity versus three representatives of the JAK inhibitor class (tofacitinib, baricitinib, and upadacitinib) based on functional assays. JAK inhibitors had suppressive activity against JAK2-dependent hematopoietic colony-forming assays modeling thrombopoiesis, erythropoiesis, and myelopoiesis; however, deucravacitinib did not. Deucravacitinib had limited potency against NK cells, cytotoxic T cells, T-helper cells, and regulatory T cells activated by JAK1/JAK3-dependent common gamma chain cytokines. These data are consistent with the biologic role of JAK1,2,3 and pharmacodynamic changes in clinical laboratory abnormalities. Against TYK2-dependent cytokines, deucravacitinib selectively inhibited Type I interferon stimulation of monocytes and dendritic cells and was a more potent inhibitor than JAK inhibitors. IL-12 and IL-23 functional outputs were similarly potently inhibited by deucravacitinib. Results are consistent with deucravacitinib selectively inhibiting TYK2.